(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The study observed the effects of flooding on socio-economic status of two integrated char lands of Jamuna River in Bangladesh during the period from March 2011-September 2011. Data were collected on primary and secondary sources. The Primary data was collected from the field level through intrinsic study and secondary data were collected from various sources vz. Bangladesh Water Development Board, Statistical Bureau, Agricultural office, published journals etc. The questionnaire survey was conducted on the char lands people in order to reveal their perception regarding effects of flooding and management and adaptation strategies. The study revealed that floods have long-term negative implications on socio-economic status. According to survey followed by the most affected sector was agriculture (53.33%), followed by health (17.77%) and property (26.66%), diseases as Diarrhea occurred at alarming levels (77.77%). In the year 2011 the crop damage (57.77%) and house damage wise significant (26.66%) and roads communications were also highly affected by flood. The study obtained the difference-in-difference estimates the magnitude of impact of flood on socio-economic status depending on the relative flood prone area and the severity of flooding and its associated impacts. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22093 J. Environ. Sci. & Natural Resources, 6(2): 37-41 2013